Analisis Pengaruh Koordinat Akhir dan Panjang Lengan Terhadap Akurasi Posisi Pada Metode Inverse Kinematics dan Iterative - Farid Aziz Shafari; Rizal Maulana; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One of the obstacles in industrial robotics is reducing errors between robots and target points because it has a great impact in the accuracy of a robot. To improve the accuracy, optimization of existing methods is needed. Kinematics is required by industrial robots to calculate the angle to get the specified position. To find out how much angle needed, Inverse Kinematics method is used by putting the target point into the calculation then the result is the angle to be reached by each joint. But, in reality, after the resulted angle being put again in Forward Kinematic equation, the result is not the same as the initial target. From this problem, Cyclic Coordinate Descent (CCD) method is created to solve it. CCD method works with iterative approach, which moves the joint one by one based on the distance of the end-effector to the target. Results from experiments using SCARA robot and 2 kinds of testing showed that CCD method could reduce the average error between end-effector and target up to 20% than Inverse Kinematic method. However, CCD method requires 0.31505 seconds longer than Inverse Kinematic due to its iterative behavior. From the results, it can be concluded that the CCD method with SCARA is effective enough to reduce the accuracy error when moving to the target position.